Acute compartment syndrome of the extremities: an update. Issue 4 (August 2018) - Papachristos, Ioannis V.; Giannoudis, Peter V.
Abstract: Acute compartment syndrome (ACS) remains a significant clinical problem with multiple health-related implications to the patient. It also carries intractable social and healthcare cost. Extensive research over the years has clarified its pathophysiology, however delays in diagnosis still persist leading to devastating consequences. Prompt and adequate fasciotomies remain the cornerstone of treatment. While diagnostic methods continue to evolve, clinical signs continue to be the most commonly used diagnostic tool for this condition. Evidence suggests that some cases are missed while many others may be overtreated. All trauma and orthopaedic surgeons will deal at least once in their career with this clinical entity affecting the extremities. Consequently, up-to-date awareness of current diagnostic and treatment developments and ongoing vigilance not to miss ACS is of paramount importance.